2016
DOI: 10.1017/s1751731115001421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a topical anaesthetic formulation on the cortisol response to surgical castration of unweaned beef calves

Abstract: Impracticality and cost of existing pain management strategies during surgical castration of beef cattle have limited their widespread implementation on-farm. A farmer-applied topical anaesthetic formulation, originally developed and used commercially to mitigate the pain of mulesing in lambs, was investigated for its potential use for managing pain in surgically castrated calves. This formulation contained lidocaine, bupivacaine, adrenalin and cetrimide. In this study, 24 Angus bull calves were randomly alloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…Importantly, it was observed that best results were obtained in the group of lambs where the tail was excised without stitching, and the wounds were treated with PR. This accords with reports that PR improves wound healing in aversive husbandry procedures conducted in Australia, including mulesing [17] and tail docking [10] of lambs and castration of calves [31]. Of note is that these studies were conducted in extensively-raised animals, and there was no evidence of delayed wound healing due to high rates of infection.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Importantly, it was observed that best results were obtained in the group of lambs where the tail was excised without stitching, and the wounds were treated with PR. This accords with reports that PR improves wound healing in aversive husbandry procedures conducted in Australia, including mulesing [17] and tail docking [10] of lambs and castration of calves [31]. Of note is that these studies were conducted in extensively-raised animals, and there was no evidence of delayed wound healing due to high rates of infection.…”
Section: Discussionsupporting
confidence: 84%
“…However, there is some controversy on the application of cortisol in studies of pain, considered as an indirect measure of stress, not pain. The handling and short-term removal of the lamb from the dam to carry out tail docking is an important source of stress to the lamb [19], and stressors such as restraint or social isolation increase cortisol levels in sheep [31].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study investigating the effect of the original TA formulation (Tri-Solfen ® Bayer HealthCare Animal Health Inc., Sydney, Australia) for castration of 3-mo Angus bull calves reported a similar effect of handling and procedural pain on cortisol response [42]. There was no difference in cortisol concentration at 0.5 or 1 h post-castration with or without post-operative TA application [42].…”
Section: Discussionmentioning
confidence: 95%
“…The need for provision of a practical method of delivering pain relief in livestock systems has been recognised for over a decade in Australia. Following extensive research, the topical anaesthetic gel Tri-Solfen ® (Bayer Animal Health, Pymble, NSW, Australia), containing lignocaine and bupivacaine, is now commercially available for use during various livestock husbandry procedures, including application to mulesing and tail docking wounds in lambs [ 3 , 4 , 5 ] and for surgical castration wounds in both lambs and calves [ 3 , 6 , 7 , 8 ]. Similarly, for practical reasons, a buccal gel formulation of the non-steroidal anti-inflammatory drug (NSAID) meloxicam, Ilium ® Buccalgesic OTM (Troy Laboratories, Glendenning, NSW, Australia), is registered for use during surgical castration of lambs [ 9 ] and calves and tail docking of lambs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%